Pengevaluasian Kelengkapan dan Performance Unit Internal Audit - Putri Alansari, I Gusti Ayu (E-Jurnal Akuntansi, 2024)
This research evaluates the completeness and performance of the internal audit unit at PT Gama Multi Usaha Mandiri. This research is qualitative research using primary and secondary data. Primary data comes from in-depth interviews and observations. In-depth interviews were conducted with directors, internal audit units and auditees. Meanwhile secondary data comes from document analysis. The data analysis technique used is a case study approach, namely comparative patterns and descriptive or explanatory preparation. The evaluation results show that the completeness and performance of the internal audit at PT Gama Multi Usaha Mandiri partially meets the International Standards for Professional Practice of Internal Audit by IIA. The internal audit unit of PT Gama Multi Usaha Mandiri is considered to have been able to maximize performance within the company even though there are still several weaknesses. This research makes a practical contribution to PT Gama Multi Usaha Mandiri and policy-wise through consideration of internal audit professional policies.